2016
DOI: 10.14710/ijred.5.1.49-55
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Prototype Cylindrical Parabolic Solar Collector for Water Heating Application

Abstract: Concentrating collectors absorbs solar energy and convert it into heat for generating hot water, steam at required temperature, which can be further used for solar thermal applications. The developing countries like India where solar energy is abundantly available; there is need to develop technology for harnessing solar energy for power production, but the main problem associated with concentrating solar power technology is the high cost of installation and low output efficiency. To solve this problem, a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The experimental results were recorded every 1 hour and the thermal performance was presented in Figs. (8)(9)(10)(11)(12)(13)(14) for different days at the same flow rate of water. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results were recorded every 1 hour and the thermal performance was presented in Figs. (8)(9)(10)(11)(12)(13)(14) for different days at the same flow rate of water. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results in Figs. (9)(10)(11) show that when using the helical tube, the output temperature, useful heat gain and thermal efficiency increase by 27.3%, 29.6% and 35.2%, respectively as compared with the straight tube. Therefore, it can be concluded that the helical tube with tracking system is more efficient than the straight tube.…”
Section: Resultsmentioning
confidence: 99%
“…where N is the number of coils turns The concentration ratio is an important parameter to describe the amount of solar energy that can be concentrated by a parabolic cylinder collector. The geometric concentration ratio is defined as the ratio between the area of the collector opening and the surface area of the coil pipe (absorber), calculated using the following equation [17]:…”
Section: The Design Of a Parabolic Cylinder Collector Type Water Heater A Determination Of Parabolic Equations As A Basis For Collector Dmentioning
confidence: 99%
“…This indicator, the Solar Water Heater Effectiveness Indicator, or SWHEI, is based on equipment deployment (installed capacity per capita, installed capacity growth) and the solar energy potential of each country. The indicator is constructed using A significant body of research focuses on the technoeconomic and life-cycle analysis of SWH technologies (Li, Tzameret, & Onyina, 2012;Chang K. , Lin, Lee, & Chung, 2008;Chang K. , Lin, Lee, & Chung, 2009;Huang, Castán Broto, & Liu, 2018;Baccouche, 2014;Handayani & Ariyanti, 2012;Kulkarni, 2016;UNEP, 2015). However, there are fewer research papers related to measuring the effectiveness of public policies that are aimed at increasing the deployment of renewable energy, much less that of SWH (Puig & Morgan, 2013;Chang, Ho, & Hsu, 2013;Held, Ragwitz, & Haas, 2006).…”
Section: Introductionmentioning
confidence: 99%